Whole-genome sequencing as an alternative to analyze copy number abnormalities in acute myeloid leukemia and myelodysplastic syndrome. Issue 10 (24th August 2022) - Lyu, Xiaodong; Li, Tao; Zhu, Dandan; Cheng, Yuexin; Chen, Yan; He, Xiangxiang; Li, Zhenling; Li, Shiyong; Wu, Wei; Geng, Shuaipeng; Zhang, Mengna; Yao, Chunxiao; et al.
Abstract: Copy number aberrations (CNA) are the core determinants for diagnosis, risk stratification and prognosis in acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). In this study, a shallow whole-genome sequencing-based assay, LeukoPrint, was utilized to depict genomic CNA profiles from the bone marrow of 137 newly diagnosed AML/MDS patients. It demonstrated 98.1% concordance of CNA profiles with cytogenetics and/or fluorescence in situ hybridization (FISH). It is advantageous in detecting CNAs of short segments (1 Mb) and from samples with low leukemic cell content, more accurate for describing complex karyotypes and less confounded by subjective bias. LeukoPrint improved the overall diagnostic yield by redefining the risk categories for 16 patients by presenting new information. In summary, LeukoPrint provided an automated, convenient, and cost-effective approach to describe genomic CNA profiles. It brought greater diagnostic yield and risk stratification information by incorporating into the routine cytogenetics based on the CNA-related criteria of standard ELN/IPSS-R guidelines.